(untitled) (Journal of Economic Research & Business Administration, 2022)
The strategy and tactics of the development of small and medium entrepreneurship (SME) is a great importance in the economic development of the country. Innovative, social directions of development depend on accurately developed strategies and tactics. The purpose of this article is to identify trends in the development of SME in the Republic of Belarus at the present stage of development. Based on this, the tasks are to highlight program and forecast documents in the field of SME development. The main hypothesis is that the state recognizes the importance and significance of SME for the socio-economic development of the Republic of Belarus at the strategic and tactical levels of public administration. A comparative analysis of the main provisions of the Strategies for the development of SME of the Republic of Kazakhstan and the Republic of Belarus has been made. The study showed the similarity of the document in the main areas. The main medium-term programs of the Republic of Belarus have sections and directions regarding SME. The results of the study can be used by the Ministry of Economy of the Republic of Belarus and other interested ministries in the development of state policy in the field of SME. Key words: small and medium entrepreneurship, strategy, government policy, government support